2012
DOI: 10.1021/la303655s
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Directed Assembly of Block Copolymer Vesicles in the Lab-on-a-Chip

Abstract: We demonstrate a microfluidic approach to the production of block copolymer vesicles via flow-directed self-assembly in a segmented gas-liquid device. Chemical conditions that favor spherical micelles in the bulk are found to yield a nearly pure population of vesicles on a chip-a transformation of two full morphological steps-because of a coalescence mechanism enabled by high shear. The production of polymeric vesicles via top-down control in a microfluidic device enables new processing routes to applications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 33 publications
(63 reference statements)
1
70
0
Order By: Relevance
“…In our group, we have applied gas–liquid two-phase microfluidic reactors to the production of a wide range of PNP systems, 42 44 , 71 74 including semicrystalline PCL- b -PEO PNPs for drug delivery. 45 47 , 75 Within these reactors, counter-rotating vortices within the liquid phase enhance mixing and introduce flow-variable high-shear “hot spots” which provide top-down control of multiscale structure, 42 including the size, 43 morphology, 44 and internal crystallinity 45 of the resulting PNPs.…”
Section: Introductionmentioning
confidence: 99%
“…In our group, we have applied gas–liquid two-phase microfluidic reactors to the production of a wide range of PNP systems, 42 44 , 71 74 including semicrystalline PCL- b -PEO PNPs for drug delivery. 45 47 , 75 Within these reactors, counter-rotating vortices within the liquid phase enhance mixing and introduce flow-variable high-shear “hot spots” which provide top-down control of multiscale structure, 42 including the size, 43 morphology, 44 and internal crystallinity 45 of the resulting PNPs.…”
Section: Introductionmentioning
confidence: 99%
“…All SN-38-PNPs are manufactured using a two-phase gas-liquid microfluidic reactor, which has been described previously by our group. 15,16,[18][19][20][21][22][23][24][25][26][27][28] An interesting feature of this reactor are the highshear "hot spots" in the corners of the liquid plugs which provide flow-variable processing of PNPs downstream of water/copolymer mixing and the resulting self-assembly. In previous work, we demonstrated that changes in the manufacturing flow rate within the microfluidic channels allow the maximum shear rate to be varied, 28 enabling shear processing control of sizes, 20,21 morphologies, 15,22 and drug delivery properties 15,16,18,19,26 of various PNP materials.…”
Section: R a F Tmentioning
confidence: 99%
“…Moffitt's group developed a gas–liquid microfluidic reactor to produce polystyrene‐ block ‐poly(acrylic acid) (PS‐ b ‐PAA) micelles with various morphologies by employing the ultrahigh‐shear field at the corners of the gas−liquid segmented liquid plugs . These on‐chip shear “hot‐spots” provided a flow‐directed top‐down means to control micelle morphology, by inducing the coalescence/fission of micelles that are meant to possess different off‐chip morphologies and thermodynamic stabilities.…”
Section: Microfluidics For Fabrication Of Sddss With Well‐controlled mentioning
confidence: 99%